Epitaxial Ge Solar Cells Directly Grown on Si (001) by MOCVD Using Isobutylgermane - Kim, Youngjo; Kim, Kangho; Lee, Jaejin; Kim, Chang Zoo; Kang, Ho Kwan; Park, Won Kyu (Journal of the Korean Physical Society, 2018)
Epitaxial Ge layers have been grown on Si (001) substrates by metalorganic chemical vapor deposition (MOCVD) using an isobutylgermane (IBuGe) metalorganic source. Low and high temperature two-step growth and post annealing techniques are employed to overcome the lattice mismatch problem between Ge and Si. It is demonstrated that high quality Ge epitaxial layers can be grown on Si (001) by using IBuGe with surface RMS roughness of 2 nm and an estimated threading dislocation density of 4.9 × 107 cm −2. Furthermore, single-junction Ge solar cells have been directly grown on Si substrates with an in situ MOCVD growth. The epitaxial Ge p-n junction structures are investigated with transmission electron microscopy and electrochemical C-V measurements. As a result, a power conversion efficiency of 1.69% was achieved for the Ge solar cell directly grown on Si substrate under AM1.5G condition.
Keywords: Epitaxial growth; Ge on Si; Isobutylgermane; MOCVD; Solar cell